Perjalanan Menjadi Cina Benteng: Studi Identitas Etnis di Desa Situgadung - Zaini, Muhammad Reza (UI Scholars Hub, 2014)
This article argue that “Chinese-ness” is an achievable entity to a social group with indigenous cultural identity. Previous studies tend to define ethnic identity as a single and objective entity. This study offers a new understanding on ethnic identity. Identity is defined as a process to identify a certain collectivity in which an individual feels he/she belonged to, while ethnicity is one of the manifestations of collectivities. Thus, identity is a subjective process, where each individual plays a significant role in determining his/her collectivity as his/her alter-ego. While ethnicity is an objective process, in which the society determine an individual’s collectivity. This qualitative research is conducted by interviewing seven informants with grounded approach, in which the researcher tries to build concepts from the collected data. This study pinted out that Cina Benteng is the whole community of Peranakan Chinese living in the countryside of Tangerang. However, some of its communities rejected that notion, and identified themselves as “orang keturunan”, a term which bought them closer to the indigenous identity. Through a long process, as a result of historic, infrastructure, demographic, and economic change, they eventually identified themselves as Cina Benteng, a term which bought them closer to the Chinese identity.